2019
DOI: 10.1136/bcr-2019-230816
|View full text |Cite
|
Sign up to set email alerts
|

Morphea masquerading as cellulitis

Abstract: A case of morphea postbreast reconstruction is presented. It is a rare condition that can be easily mistaken for other inflammatory conditions or infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Review of the available literature revealed one recent report of morphea being mistaken for cellulitis after breast reconstruction surgery [6]. The patient presented with non-tender, noninflamed erythematous skin lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Review of the available literature revealed one recent report of morphea being mistaken for cellulitis after breast reconstruction surgery [6]. The patient presented with non-tender, noninflamed erythematous skin lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Morphea may be mistaken for infections, particularly in the active stage of disease. It has been mistaken for cellulitis and tinea cruris [6,7]. Zosteriform morphea, a rare type of morphea that occurs in a dermatomal distribution, has also been reported [8].…”
Section: Discussionmentioning
confidence: 99%